2009
DOI: 10.1016/j.concog.2008.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Th.o.m.a.s.: An exploratory assessment of Theory of Mind in schizophrenic subjects

Abstract: a b s t r a c t A large body of literature agrees that persons with schizophrenia suffer from a Theory of Mind (ToM) deficit. However, most empirical studies have focused on third-person, egocentric ToM, underestimating other facets of this complex cognitive skill. Aim of this research is to examine the ToM of schizophrenic persons considering its various aspects (first-vs. second-order, first-vs. third-person, egocentric vs. allocentric, beliefs vs. desires vs. positive emotions vs. negative emotions and how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
60
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 49 publications
1
60
0
1
Order By: Relevance
“…The large degree of heterogeneity of ToM findings could be explained by the state variables and task differences, as was shown in a meta-analysis (Bora and Pantelis, 2013). In addition, it was demonstrated that the ToM deficit is not uniform in individual patients and is distributed varyingly among different components of ToM (Bosco et al, 2009). This opens the question of possible associations between the ToM impairment and psychopathology and/or cognitive functioning in schizophrenia.…”
Section: Theory Of Mindmentioning
confidence: 99%
“…The large degree of heterogeneity of ToM findings could be explained by the state variables and task differences, as was shown in a meta-analysis (Bora and Pantelis, 2013). In addition, it was demonstrated that the ToM deficit is not uniform in individual patients and is distributed varyingly among different components of ToM (Bosco et al, 2009). This opens the question of possible associations between the ToM impairment and psychopathology and/or cognitive functioning in schizophrenia.…”
Section: Theory Of Mindmentioning
confidence: 99%
“…Using the Theory of Mind Assessment Scale (Bosco et al, 2009) In a more recent study by Maurage et al (2015) just over half the AD participants" performed significantly worse than controls across both a simple and more complex belief-tracking task. They found that disease-related factors (years of illness, units of alcohol consumed) was negatively related to AD participants" ability to track…”
Section: Introductionmentioning
confidence: 99%
“…The Th.o.m.a.s. interview (Bosco et al, 2009) is meant to investigate the retrospective facet of ToM, based on a theoretically-driven decomposition thereof that aims at bringing its diversity and complexity into light. There is no way of doing this without recurring to the interviewee's deliberate introspection and discursive abilities.…”
mentioning
confidence: 99%